META ANALISIS: PENGARUH CAPSAICIN PADA SISTEM PENCERNAAN AVES: META ANALISIS: PENGARUH CAPSAICIN PADA SISTEM PENCERNAAN AVES - Haria, Yesaya; Arara, Fakhriya Bilad; Afriani, Arikah Putri; Rusdi,; Lisantie, Elsa (Jurnal Peternakan Nusantara, 2024)
The use of antibiotic growth promoters has been banned in various countries because of the risk of causing bacterial resistance to drugs and antibiotic residues, so phytobiotics are used as an alternative. One of the many commercial products known to have the potential to be used as a phytobiotic is the capsicum group. The characteristic of Capsicum is the high content of the capsaicin compound in it which is famous for its pharmacological abilities including increasing livestock production. This research is a meta-analysis research conducted to determine the effect of using capsaicin on poultry digestion. The data used in this research is secondary data extracted from previously collected journals. The data collected was then subjected to a statistical difference test to determine the differences between each treatment. The results of the analysis showed that in general the use of capsaicin supplementation increased digestive enzyme activity, feed intake, and chicken weight compared to treatment without the use of capsaicin. The statistical test results also showed that there were differences in the results of each treatment as indicated by a p value of 0.011 < 0.05 and there was a real and significant influence from the use of capsaicin on digestive assessment parameters with a p value of 0.011 < 0.05. These results show that capsaicin can be used as an alternative antibiotic for poultry to increase digestive enzyme activity, feed digestibility, increase feed intake, and increase bird body weight.